PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN PENGETAHUAN GANGGUAN KOMUNIKASI PASCA STROKE DI WILAYAH JATI RANGGA TAHUN 2023 - Liza Laela Abida; Aril Sudarsono; Nina Mustikasari (IFI cabang Kota Bekasi, 2023)
Background: Stroke is a functional brain disorder that occurs suddenly with focal or global clinical signs that last more than 24 hours. Stroke can result in functional disorders of the human body's organs, one of which is the speech organ which can cause speech or communication disorders. Objective: This activity aims to increase understanding of post-stroke communication disorders and their prevention among the community in RT 003 Jatirangga Village.Methods: This service activity uses 3 methods which include identifying problems, providing interventions, and conducting evaluations. Results: Sampling was carried out by means of nonprobability sampling with accidental sampling technique. After conducting an evaluation at the last meeting, then the data was processed with a computer program indicating that there was a lack of understanding about stroke and people with stroke risk factors. Conclusion: there is a lack of understanding and people with risk factors for stroke so that they are given health education as a form of promotion and stroke exercise as a form of prevention. Keywords: Community RT 003 Kelurahan Jatirangga, Health Counseling and Prevention communication disease after stroke